Performance of Reinforced Stone Column using Geotextile & Geogrid Encasements in Triaxial Test - M. Nasiri; M. Hajiazizi (مهندسی عمران شریف, 2021)
The use of stone columns is one of the effective ways to increase the bearing capacity of soils. An alternative system that can provide sufficient lateral confinement to support stone columns and increase bearing capacity is geosynthetic encased stone columns. These methods have been well utilized in Europe and South America. If the soil bed requires excessive confinement, the use of geotextile and geogrid encase around the stone columns is one way to improve the performance of these load-bearing members. This study aims to compare the behavior of geotextile and geogrid layers in reinforcing stone columns in standard Ottawa sand. In this study, a series of triaxial experiments in the undrained state was used. In the lowest confining pressure case, the load-bearing capacity for the geotextile reinforced column will be 1.18 times higher. Whereas for the geogrid-reinforced stone column, the load-bearing capacity is 1.31 times higher. In this study, standard Ottawa sand, gravel with a unit weight of 17 kN/m3 and a friction angle of 47.8°, geotextile and geogrid layers, and triaxial test apparatus are used. Triaxial specimens were 10 cm in diameter and 20 cm in height. Stone column dimensions of 2 cm in diameter and 20 cm in height are selected, respectively. Due to the limitations in the laboratory and the simulation of natural conditions, the unit weight of sand samples and stone columns made in triaxial test molds were selected as 15 and 17 kN/m3, respectively. Precipitation is used to fabricate cylindrical sand samples for triaxial testing. In this method, firstly attach the membrane to the underside of the triaxial apparatus and fasten the detachable bifurcation mold to the membrane and attach the membrane to the detachable mold walls by suction pumping about 2 bars. The aim is to create a homogeneous sample with uniform rainfall velocity to obtain a sample with evenly possible porosity. The method of precipitation depends on two parameters, one is the intensity of rainfall (amount of sand poured in a given volume at a specified time), and the other is the height of the sand fall, which is the distance between the sand outlet from the precipitation tank to the sand bed. The important point is that to achieve the same porosity, and this distance must be kept constant throughout the precipitation process. After construction, the test is performed according to ASTM D7181-11. Triaxial CU experiments on Ottawa sand were carried out in three cases: unreinforced, reinforced using geotextile encased stone column and reinforced using geogrid encased stone column. In triaxial experiments, three confining pressures of 200, 300, and 400 kPa were used.